2023
DOI: 10.1039/d3me00102d
|View full text |Cite
|
Sign up to set email alerts
|

Two-photon microprinting of 3D emissive structures using tetraazaperylene-derived fluorophores

Abstract: A new class of fluorophores based on a twisted tetraazaperylene core has been employed in the fabrication of emissive organic 3D microstructures using two-photon laser printing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…1) as emitters at high concentrations in solution as well as in condensed thin films and their application as fluorophores in two-photon microprinted 3D emissive structures. 34…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1) as emitters at high concentrations in solution as well as in condensed thin films and their application as fluorophores in two-photon microprinted 3D emissive structures. 34…”
Section: Introductionmentioning
confidence: 99%
“…1) as emitters at high concentrations in solution as well as in condensed thin films and their application as fluorophores in two-photon microprinted 3D emissive structures. 34 Formally, the OAPPDO compounds may be viewed as tetraazaperylenes that are decorated with N-substituted urea units in both opposite peri-positions. In particular, we found that the facile modification of these fluorophores in the bay-positions enables efficient tuning of their luminescent properties.…”
Section: Introductionmentioning
confidence: 99%